Ta có:
\(\frac{2009^{2008+1}}{2009^{2009+1}}=\frac{2009^{2009}}{2009^{2010}}=\frac{1}{2009}\)
\(\frac{2009^{2008+5}}{2009^{2009+9}}=\frac{2009^{2013}}{2009^{2018}}=\frac{1}{2009^5}\)
=>Đẳng thức trên lớn hơn đẳng thức dứi(vì 2009<2009^5)
Vậy.......
Ta có:
\(\frac{2009^{2008+1}}{2009^{2009+1}}=\frac{2009^{2009}}{2009^{2010}}=\frac{1}{2009}\)
\(\frac{2009^{2008+5}}{2009^{2009+9}}=\frac{2009^{2013}}{2009^{2018}}=\frac{1}{2009^5}\)
=>Đẳng thức trên lớn hơn đẳng thức dứi(vì 2009<2009^5)
Vậy.......
so sánh \(\frac{2009^{2008}+1}{2009^{2009}+1}\)và \(\frac{2009^{2008}+5}{2009^{2008}+9}\)
so sánh 2 phân số : \(A=\frac{2008^{2009}+2}{2008^{2009}-1};B=\frac{2008^{2009}}{2008^{2009}-3}\)
thực hiện tính và so sánh A=\(\frac{2008^{2009}+1}{2009^{2009}+1}\)và B=\(\frac{2009^{2009}+1}{2009^{2010}+1}\)
So sánh \(\frac{2008}{2009}+\frac{2009}{2010}và\frac{2008+2009}{2009+2010}\)
so sánh A= \(\frac{2009^{2008}+1}{2009^{2009}+1}\)và B= \(\frac{2009^{2009}+1}{2009^{2010}+1}\)
So sánh : \(A=\frac{2008}{2009}+\frac{2009}{2010}+\frac{2010}{2011}vàB=\frac{2008+2009+2010}{2009+2010+2011}\)
So sánh
A=\(\frac{2009^{2008}+1}{2009^{2009}+1}\) và B= \(\frac{2009^{2009}+1}{2009^{2010}+1}\)
So sánh
(2008^2009+1)/ (2008^2009-1) và (2008^2009)/ (2008^2009-3)
So sánh : A = \(\frac{2009^{2008}+1}{2009^{2009}+1}\)với B = \(\frac{2009^{2009}+1}{2009^{2010}+1}\)